Interactive Workshop on Metal Casting Aluminum Material for Productive Teachers of SMK Negeri 1 Bukittinggi : Workshop Interaktif Metal Casting Material Alumnium bagi Guru Produktif SMK Negeri 1 Bukittinggi - Arafat, Andri; K, Arwizet; Rifelino, Rifelino; Abadi, Zainal Abadi (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
This technology is one of the technologies that is widely used in the industrial sector, especially large industries and the automotive industry. Automotive products, machine components and household appliances are widely made using this metal casting method. Metal casting is a technique in applying a product design or making machine products/components, motorbikes and others. Metal Casting Technology is something new for teachers at SMK Negeri 1 Bukittingi. This community service activity was initiated to upgrade teacher skills in understanding metal technology to teachers at Vocational High Schools so that the skills they have are more developed in designing 3-dimensional objects and realizing them in the form of real products. It is hoped that through the training given to teachers at SMK, they can stimulate creative ideas in drawing techniques using CAD software and realizing them in the form of automotive component products. This Metal Casting Workshop is also a Downstream of research that has been carried out with previous funding. Thus, this activity is very relevant to the research results and partner needs, so that the achievements and benefits generated, in addition, the service that will be carried out is also an official request from SMK Negeri 1 Bukittinggi. In general, the activity went smoothly and achieved the goals set in this community service activity